Porto : an urban area on the way to happiness - Monteiro, Ana (2009)
All available information indicates that the urban areas will continue to be the most preferred areas to live by human beings for decades to come. And why are they preferred? At a time when all the descriptions insist in the dark side of this gloomy urban modus vivendi, it is relevant to ask whether there is any masochism or if it is in fact a rational and logical option. Using the example of Porto, we intend to illustrate how this preference is a logical and rational strategy for finding happiness. Despite the multiple dimensions of happiness - health, basic needs’ satisfaction, feelings, freedom, safety, time, culture, entertainment, etc. - are more likely to be met in an urban area, it is not easy to offer/plan a product that accomplish the desire of all. Happiness is a complex formula of several objective and subjective dimensions. Planners may ensure provision of employment, security, environmental quality, leisure and recreation spaces, and facilities for education, health or sports, which meet the objective dimension. However, in the field of feelings or cultural/historical skeleton or attitudes towards life, the interference of the planners is more induced than offered. We will try to validate, using Porto’s case study, some of the positive and negative impacts created by the presence or absence of a certain blend of happiness inductor factors (i.e. neighbourhoods’ size, green spaces, transports, health, climate, etc.).